The Correlation between the Leadership Roles of The Head of PHC and Work Discipline in PHC Employees - Cindy Wulandari; Rapotan Hasibuan (Universitas Nahdlatul Ulama Surabaya, 2023)
Based on a preliminary study in February 2022 at the Medan Sunggal Primary Health Care (PHC), some PHC employees had inadequate work discipline. They did not comply with working hours. In addition, employee absence increased in the last three months of 2022. In addition, 10% of them still did not obey the regulation, such as not wearing uniforms and using sandals at work. This research analyzes the correlation between the leadership roles of the head of PHC and work discipline in PHC employees. This paper was quantitative research using a descriptive-analytic approach with a cross-sectional study design. The population was all employees working at the Medan Sunggal PHC. There were 43 respondents with the total sampling method. The dependent variable was work discipline in PHC employees. Meanwhile, the independent variable was the leadership roles of the head of PHC, with sub-variables communication, direction and guidance, supervision, motivation, and rewards. The instrument utilized a questionnaire. Data analysis used Spearman rank correlation statistical tests with α=0.05. Communication, direction, and guidance were strongly associated with work discipline, with p-value each 0.000 and 0.000. Supervision had a weak correlation with work discipline with p=0.000. However, motivation and awards negatively correlated with p-value sequentially 0.000 and 0.006. The leadership roles of the head of PHC are associated with work discipline in PHC employees. The head of PHC should perform well in communication, direction and guidance, supervision, motivation, and awarding to improve work discipline in employees.